2008
DOI: 10.18433/j3np48
|View full text |Cite
|
Sign up to set email alerts
|

Bioequivalence assessment of topical clobetasol propionate products using visual and chromametric assessment of skin blanching

Abstract: -PURPOSE. The assessment of the degree of skin blanching following the application of a formulation containing a topical corticosteroid has been established as a surrogate method for the determination of bioequivalence. In this study, both visual and chromametric assessments have been carried out on two topical creams containing clobetasol propionate (0.05%) and the results from both methods are compared. METHODS. Human subjects (volunteers) were screened using a cream containing 0.05% clobetasol propionate, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…AUC test /AUC ref ratios obtained from the abovementioned pilot study TS profiles indicated that the test and reference product showed the same outcome as that found with data previously obtained using the HSBA (Table 1)to assess identical products (21). On the basis of these data, pivotal TS studies were undertaken as described in section 2.3 using 30 subjects to provide a power of at least 80%.…”
Section: Pilot Studysupporting
confidence: 70%
See 1 more Smart Citation
“…AUC test /AUC ref ratios obtained from the abovementioned pilot study TS profiles indicated that the test and reference product showed the same outcome as that found with data previously obtained using the HSBA (Table 1)to assess identical products (21). On the basis of these data, pivotal TS studies were undertaken as described in section 2.3 using 30 subjects to provide a power of at least 80%.…”
Section: Pilot Studysupporting
confidence: 70%
“…The same formulation, Dermovate ® cream, was used as the reference and test product. TS data were compared with data obtained from an HSBA study (21) on the same product.…”
Section: Subjects and Study Designmentioning
confidence: 99%
“…Upon comparing the product to itself, the results of AUC corr values showed similar confidence intervals and AUCtest/AUCref ratios using untransformed (Locke's) and also log-transformed data as shown in Table 2. It is interesting to note that the results are similar to those of a previously conducted pivotal HSBA study (Au et al, 2008). Hence, the TS method is seen to be comparable to the HSBA method, as it produced the same bioequivalence outcome.…”
Section: Dermatopharmacokinetic Methods Also Known As Tape Stripping supporting
confidence: 77%
“…The skin blanching profiles shown below were very similar when comparing the data between the two different assessment methods, or between "detectors" and "nondetectors" (Au et al, 2008).…”
Section: Study Designsmentioning
confidence: 77%
“…However, with respect to sampling of drug molecules from the skin, perturbation of blood flow to the local tissue is critical which would recover to normal in approximately two hours. The technique has been successfully adopted and demonstrated for dermatological research as well as for demonstrating the bioequivalence of topical dosage forms [19]. Dermal Microdialysis (DMD) is a relatively new application of microdialysis which allows continuous monitoring of endogenous and/or exogenous solutes in the interstitial fluid (ISF) of dermal tissue with minimal tissue trauma and involves the placement of small perfused membrane systems at given depths within the dermis.…”
Section: Microdialysismentioning
confidence: 99%